Pengaruh penanaman modal dalam negeri, penanaman modal asing, utang luar negeri dan surat berharga syariah negara terhadap perekonomian Indonesia - Pratama, Dyah Novi; Rofiuddin, Mohammad (Nur Science Institute, 2023)
Economic growth is the primary objective to enhance the quality of human resources, societal welfare, and equitable national development within a country. Investment is considered a key determinant in achieving sustainable economic growth. Moreover, to meet developmental expenditure needs, governments often resort to borrowing. Therefore, this study investigates the impact of domestic investment, foreign investment, foreign debt, and state Islamic securities on Indonesia's economic growth. By utilizing secondary data from various reputable statistical institutions such as the Central Bureau of Statistics (BPS), the Fiscal Policy Agency (BPKPM), Bank Indonesia (BI), and the Financial Services Authority (OJK) spanning from 2012 to 2022, this research aims to provide a deeper understanding of the factors influencing Indonesia's economic growth. Multiple Linear Regression analysis is employed to analyze the data in this study. The results indicate that domestic investment does not significantly affect Indonesia's economic growth, while foreign debt is found to have a significant impact on economic growth. However, no evidence exists that state Islamic securities influence Indonesia's economic growth.